Wound healing potential of topical bacteriophage therapy on diabetic cutaneous wounds. - Mendes, João J.; Leandro, Clara; Corte-Real, Sofia; Barbosa, Raquel; Cavaco-Silva, Patrícia; Melo-Cristino, José; Górski, Andrzej; Garcia, Miguel (Wound Repair & Regeneration)
Chronic wounds that fail to heal are a common complication of diabetes mellitus and the most common precipitating reason for nontraumatic lower limb amputation. Unfortunately, the bacterial species that cause these infections are becoming more resistant to antibiotics, making them increasingly difficult to treat. We assessed the feasibility of combating chronic bacterial infections with a topically delivered bacteriophage cocktail in two animal models of diabetes mellitus. Microbiological, planimetric, and histological parameters were compared in debrided infected wounds with or without topical bacteriophage treatment. We determined that bacteriophage treatment effectively decreased bacterial colony counts and improved wound healing, as indicated by smaller epithelial and dermal gaps, in Staphylococcus aureus and Pseudomonas aeruginosa infections but was not as effective against Acinetobacter baumannii. Although the improvements were more significant in the rodent model than in the porcine model, our results suggest that topically administered bacteriophage treatment may be effective in resolving chronic infections, especially when applied in conjunction with wound debridement. These findings have important implications for the feasibility of using topical antimicrobial therapies to safely treat chronic infections in diabetes mellitus patients.